The State of Modern South Korean Animal Cruelty Law: An Overview with Comparison to Relevant United States and Swiss Law and the Future - Andrew Alberro (Washington University Global Studies Law Review, 2019)
On April 21, 2012 a picture surfaced on the internet showing a beagle dog tied to the back of a Hyundai Equus. The dog was disemboweled, having died from being dragged behind the car at high speeds along a highway in Seoul, South Korea. Upon investigation, the owner claimed that the dog’s death was an accident, and police did not press charges due to insufficient evidence of intentional harm. Many South Koreans were outraged at the lack of repercussions for the car owner, and the event caused heated discussion on the effectivity of the Animal Cruelty Provision of the Animal Protection Act. The ‘Devil’s Equus’ incident, as it became known, would not be the first or last time this happened in South Korea. ‘Devil’s Equus 2’, ‘3’, and ‘Devil’s Truck’ are just a few more examples of similar incidents following the original, that all ended with similar results. Acts of animal cruelty including hoarding, physical abuse, and neglect often go unpunished in South Korea due to a combination of the vague language of the law and a lack of officials willing to enforce it. Numerous viral incidents of animal cruelty have caused wide outrage and criticism of the state of current animal protection law in South Korea and in particular its enforcement. South Korean animal cruelty laws have also faced criticism internationally. Puppy mills and the dog and cat meat trade in particular have caused South Korean animal cruelty law to incur intense global scrutiny. Recently, a United States-based international animal rights welfare organization, World Animal Protection, ranked South Korean animal cruelty protection law as an overall D on their A to G scale. The organization noted that while South Korea’s Animal Protection Act offers anti-cruelty protections and enforcement mechanisms in the form of fines and imprisonment, only some animals are classified as “protected” and there is a lack of strong deterrents. Incidents such as these make clear that while South Korea has made efforts to combat animal cruelty through its Animal Protection Act, there remains a need for enhanced protections and more effective enforcement. This note is primarily focused on an examination of South Korea’s Animal Protection Act and its limitations in preventing animal cruelty. To that end, the note will briefly discuss the history of South Korea, its legal system, and the development of the first animal cruelty law. For purposes of comparison, an overview of United States and Swiss animal protection legislation will be provided followed by a comparison of their enforcement tactics. Following the international comparisons, there will be an examination of the effect of South Korean media sources, animal activism and public opinion on its animal cruelty law. Finally, the note will discuss proposed changes and recommendations for stronger animal cruelty legislation and enforcement.
Keywords: animal law; international law; comparative law; south korea; switzerland; animal cruelty; dog; canine